The Effect of Genderism on the Process and the Product of Translation (Journal of the College of Languages (JCL), 2022)
Many studies have been made and still concerning the field of translation. Since the mid-90's a considerable amount of researches has tackled the problem of gender and its effect on the process and the product of translation. Simon (1996, p 508) points out that when comparing women and men as translators and writers through history, women seem to be the weaker side. This paves the way to feminist movements which produce prominent studies concerning gender as a concept and translator's gender as practice on the quality and the accuracy of the translation. Flotow (in Meschia, 2012, p 1-4) outlines several issues that can be examined concerning gender and translation, these are historical studies, theoretical contemplations, translator's identity, post-colonial questions, and cultural questions. This research deals with two aspects of identity, i.e. gender: the gender of the translator (and its effect on the translation if there is any) and the gender of the evaluator of the translated text (and its effect if there is any). The aim of this paper is to find out whether there is any negative influence of the identity on the process and the product of translation. For this purpose, 40 students from the Department of Translation at Al-Ma'moon College University, in addition to 20 postgraduate, have been asked to assess and analyze through a questionnaire (that tackles the identity of both translator and evaluator) and an assessment of Shakespeare's Sonnet (no. 18) and four translated versions of it. The study remarkably shows that the gender-bias effect of the identity of the translator and the evaluator have an influence on students with 12.5% for undergraduate and 5% for postgraduate students. The majority of 87.5% and 95% believe that gender does not affect. This proves the research's hypothesis that there is a difference in the language of the two genders, yet it will not affect the gender of both of the translator and the evaluator.